Reverse-Engineering a Rooftop Solar Station in a Blackout - Oleksandr Gorbachenko (Emerging Frontiers Library for The American Journal of Interdisciplinary Innovations and Research, 2025)
The article examines the adaptive control as well as the compelled reverse engineering phenomenon of an autonomous solar power station in conditions of infrastructural and geopolitical crises precipitated by large-scale blackouts. The study stresses energy resilience is important, noting a rise in proprietary black boxes and absent documentation about safety-critical parts. Conflict along with disaster zones especially highlight this issue. In Odesa, engineers independently deconstructed an undocumented inverter protocol and developed a monitoring system to minimise life-safety risks. This occurred at a time of wartime outages so the research objective is for a systematic analysis of this case study. This work is novel in that it conceptualizes a Resilience, Vulnerability Nexus model, elucidating a paradox: reverse engineering locally for improvement of resilience inextricably links to globalizing vulnerabilities that were previously hidden within closed technologies. The principal findings show two cardinal engineering trade-offs converge, feasibility opposes rigour, trust opposes accuracy, as well as they also recognize that, under extreme constraints, immediate functionality with solution transparency supersedes technical perfection. Alternative algorithms for estimating battery state-of-charge are also assessed. The article will be of use to researchers in energy and cybersecurity, practicing engineers and policymakers, and system designers when they are developing decentralized and resilient energy systems.